2022
DOI: 10.3389/fendo.2022.1027686
|View full text |Cite
|
Sign up to set email alerts
|

The roles of mesenchymal stem cell-derived exosomes in diabetes mellitus and its related complications

Abstract: Diabetes mellitus is a type of metabolic disease characterized by hyperglycemia, primarily caused by defects in insulin secretion, insulin action, or both. Long-term chronic hyperglycemia can lead to diabetes-related complications, causing damage, dysfunction, and failure of different organs. However, traditional insulin and oral drug therapy can only treat the symptoms but not delay the progressive failure of pancreatic beta cells or prevent the emergence of diabetic complications. Mesenchymal stem cells have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 141 publications
0
11
0
Order By: Relevance
“…When osteoporosis occurred, the number of bone marrow mesenchymal stem cells differentiating into adipocytes increases and osteoblast generation decreases [ 35 , 36 , 37 , 38 ]; studies have shown that activation of bone morphogenetic protein 2 could inhibit adipogenesis [ 39 , 40 ]. In this study, pathological staining of bone tissue showed that the number of adipocytes in the tibial bone marrow of the DM group was markedly increased, and the number of osteoblasts was markedly decreased.…”
Section: Discussionmentioning
confidence: 99%
“…When osteoporosis occurred, the number of bone marrow mesenchymal stem cells differentiating into adipocytes increases and osteoblast generation decreases [ 35 , 36 , 37 , 38 ]; studies have shown that activation of bone morphogenetic protein 2 could inhibit adipogenesis [ 39 , 40 ]. In this study, pathological staining of bone tissue showed that the number of adipocytes in the tibial bone marrow of the DM group was markedly increased, and the number of osteoblasts was markedly decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Their immunomodulating action is considered to play a major role through the release of trophic factors. Nevertheless, studies have demonstrated that MSC culture medium produced a similar therapeutic effect to MSC therapy in retinal ischemia [ 45 ], or in diabetes mellitus [ 46 ]. Subsequent studies have highlighted the presence of EVs in the culture medium [ 47 ].…”
Section: Mesenchymal Stromal Cell-derived Extracellular Vesicles (Msc...mentioning
confidence: 99%
“…Injecting MSC-EVs locally into a murine model of retinal detachment (RD) significantly reduces levels of inflammatory cytokines TNF-α and IL-1β, Atg5 cleavage, and apoptosis of photoreceptor cells, thereby preserving the normal structure of the retina [ 310 ]. The existence of miRNAs targeting TLR4/NF-kB within MSC-EVs suppresses inflammation associated with peripheral neuropathy in a murine diabetic model by decreasing the expression of inflammatory cytokines and regulating the ratio of M1 and M2 macrophages, thereby improving neurovascular architecture [ 311 ].…”
Section: Pharmacology Of Extracellular Vesiclesmentioning
confidence: 99%